Interventions for pressure ulcers: a summary of evidence for prevention and treatment. Issue 3 (March 2018) - Atkinson, Ross; Cullum, Nicky
Abstract Study Design Narrative review. Objectives Pressure ulcers are a common complication in people with reduced sensation and limited mobility, occurring frequently in those who have sustained spinal cord injury. This narrative review summarises the evidence relating to interventions for the prevention and treatment of pressure ulcers, in particular from Cochrane systematic reviews. It also aims to highlight the degree to which people with spinal cord injury have been included as participants in randomised controlled trials included in Cochrane reviews of such interventions. Setting Global. Methods The Cochrane library (up to July 2017) was searched for systematic reviews of any type of intervention for the prevention or treatment of pressure ulcers. A search of PubMed (up to July 2017) was undertaken to identify other systematic reviews and additional published trial reports of interventions for pressure ulcer prevention and treatment. Results The searches revealed 38 published systematic reviews (27 Cochrane and 11 others) and 6 additional published trial reports. An array of interventions is available for clinical use, but few have been evaluated adequately in people with SCI. Conclusions The effects of most interventions for preventing and treating pressure ulcers in people with spinal cord injury are highly uncertain. Existing evaluations of pressure ulcer interventions include very few participants with spinal cord injury. Subsequently, there is still a need for high-quality randomised trials of such interventions in this patient population.